Overcoming cancer therapy resistance by targeting inhibitors of apoptosis proteins and nuclear factor-kappa B - Dai, Yao (e-Century Publishing Corporation, 2009)
Chemo- or radioresistance markedly impairs the efficacy of cancer therapy and involves anti-apoptotic signal transduction pathways that prevent cell death. In resistant cancer cells, both inhibitors of apoptosis proteins (IAPs) and nuclear factor-kappa B (NF-κB) play a pivotal role in preventing apoptosis triggered by a variety of stresses, facilitating them as potential targets in cancer treatment. Furthermore, mounting evidences have established the crosstalks between IAPs (eg. XIAP, cIAP-1, cIAP-2) and proteins involved in NF-κB signaling (eg. TRAF2, RIP1, TAB1). Second mitochondria-derived activator of caspases (Smac) is a mitochondrial protein that released into cytoplasm upon apoptotic stimuli. As Smac functions as an endogenous IAP inhibitor, small molecule Smac-mimetics are believed to neutralize IAPs function that results in liberating caspase activity and promoting apoptosis. Moreover, recent studies show that Smac-mimetics may kill cancer cells in a different manner, which involves inducing ubiquitination of cIAPs, regulating NF-κB signaling and facilitating TNFα-triggered, caspase-8-mediated apoptosis in a certain cancer cell types. In other cancer cells that are resistant to TNFα or chemo/radiotherapy, Smac-mimetic IAP-inhibitors can enhance ionizing radiation or tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis, indicating the potential role of Smac-mimetics in overcoming acquired therapy-resistance. Such findings provide important impetus for utilizing IAP-inhibitors as novel adjuvant therapy for the TNFα–resistant, NF-κB constitutively active cancers that account for the majority of patients who are refractory to current therapeutic approaches.